Hyperthyroid crisis with cholestasis in a 12-year-old girl: a case report - Celine Celine; Ni Made Dwiyathi Utami (Indonesian Pediatric Society, 2023)
Hyperthyroidism is considered to be an emergency in children. Death can occur in 10-20% of cases. This condition is found more often in adolescents and girls. Cholestasis may be caused by the hyperthyroidism or side effects of anti-thyroid drugs. Increased hepatic blood flow without adequate oxygen supply as a result of a hypermetabolic state affects the transport of bilirubin, leading to cholestasis.